Editorial (Inglês) - Mota, Maurício (Revista de Direito da Cidade, 2018)
DOI: 10.12957/rdc.2018.36251 The Journal of City Law, classified by MEC / CAPES as Qualis A1, Law and registered in the Web of Science, is pleased to inform all its readers that it has been classified as the 4th most important electronic journal of the country in the area of Law and as one of the 450 most important Ibero-American journals of all specialties, in the Ibero-America Journal Rankings index of Clarivate Analytics and REDIB. The new ranking incorporates a new methodology, since it not only focuses on the impact of scientific journals in the region, but also takes into account published articles. The initiative comes from the agreement of REDIB and Clarivate Analytics to consolidate a bibliographic information system that allows the generation of scientific and editorial quality indicators at the Ibero-American level. In this issue of the Journal we have also broadened our body of our reviewers / evaluators, with the inclusion of many professors, from countless states of the country and also from many foreign professors, in a total of more than 410 evaluators. We also publish, for immediate reference to the readers, the links of the various national and international indexes of journals and periodicals where our Journal of City Law is indexed. We thank, as always, all the readers, authors, evaluators and collaborators for the collaboration and trust and for the always excellent work done. We always remember that the submissions for the Journal of City Law are permanent and must be carried out by the system, directly on the Journal’s page. Good reading to all!